ChemInform Abstract: The Tetragermanates A2Ge4O9 (A: Na, K and Rb). Issue 47 (4th November 2013) - Redhammer, Guenther J.; Tippelt, Gerold
Abstract The structures of the isotypic title compounds (trigonal, space group P <![CDATA[3]]> <inline-graphic xlink:href="ark:/27927/pgg3r55zjfn" mimetype="image" xlink:type="simple" xmlns:xlink="http://www.w3.org/1999/xlink" />c1, Z = 6) are redetermined by single crystal XRD.